A tag prediction anti–collision algorithm using extra bits for RFID tag identification. (27th August 2012) - Kim, Sungsoo; Kim, Yonghwan; Choi, Wonseok; Ahn, Kwangseon
Tags have their own unique identifiers and information, and send such information to a reader; thereby the reader identifies the ID. The proposed algorithm predicts the tag ID by using the number of collided bits and the number of 1s in tag response signal. Even if tag collision occurs in the identification process, the reader identifies the RFID tag through prediction based on information provided by the extra bits. If the number of 1s to be included in collided bits is 1 or collided bits –1, the reader identifies tags as many as the number of collided bits.